Dog leukocyte antigen‐88034:01 presents nonamer peptides from canine distemper virus hemagglutinin, large polymerase, and matrix proteins - Nemec, Paige S.; Holmes, Jennifer C.; Hess, Paul R. (HLA, 2021)
Canine spontaneous cancers may offer greater fidelity than rodent models in advancing clinical immunotherapies. Boxers in particular are distinguished as study subjects by their popularity, and high incidence of human‐relevant cancers. Further, the MHC class I allele DLA‐88*034:01, with a known motif, dominates the breed, facilitating discovery of shared CTL responses against mutation‐origin neoepitopes by standard prediction methods. We experimentally confirmed the allomorph's binding motif by developing an MHC surface stabilization assay. The assay validated four DLA‐88*034:01‐presented peptides from canine distemper virus, ubiquitously administered in routine vaccines, for positive controls in future CTL studies. In turn, these viral peptides substantiated motif‐based prediction for DLA‐88*034:01. The study adds new tools for studying neoepitope‐specific CTL in Boxers to foster canine comparative oncology.